A study of the Effectiveness Components of Healthy Schools Under the office of Sakon Nakhon Primary Education Service Area 1 - Thongdonnoi, Natthawut; Pengsawat, Waro; Jantarak, Suphiran (Journal of Education Rajabhat Maha Sarakham University, 2024)
This research purposes wer to study the components of effective healthy school for educational institutions under the sakon nakhon primary educational service area office, area 1, the research was divided into 2 steps; Step 1: Synthesizing the components of effective healthy school by studying 15 sources documents and related researches which effective components of school wellbeing, totaling and Step 2: Evaluate the suitability of the effective components of school wellbeing by 5 experts, the research tools were a document synthesis form and a 5-level rating scales questionnaire. The statistics used frequency, percentage, mean, and standard deviation. The research results found that there were 5 components of the effectiveness healthy schools: 1) Happy learners, 2) Happy school, 3) Happy environment, 4) Happy family, and 5) Happy community, and all of them were appropriate and at the highest level, arranged from the highest to lowest mean scores as follows: 1) Happy School was at 4.88 2) Happy environment was at 4.74, 3) Happy learners was at 4.65, 4) Happy community was at 4.65, and 5) Happy family was at 4.62 respectively.